Estimating the population size and ecological implications of a Sula sula colony on Mona Island - Espíndola Cáceres, Walter David (2021)
Descargue el texto completo en el repositorio institucional de la Pennsylvania State University: https://etda.libraries.psu.edu/catalog/18638wde14